2020
DOI: 10.1088/1361-6641/ab74eb
|View full text |Cite
|
Sign up to set email alerts
|

Barrier coating and plasmonic effect by using diamond-like carbon and silver nanoparticles on quantum dots sensitize solar cells

Abstract: Barrier coating and plasmonic effect by using diamond-like carbon and silver nanoparticles on quantum dots sensitize solar cells. Semiconductor Science and Technology, 35(4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The embedded of Ag on the DLC lattice prevents the agglomerated nanoparticles and the growth of large and clustered nanoparticles. Our previous reports have shown that the effect of gold and silver nanoparticles in the DLC lattice has led to increased e ciencies in quantum dot solar cells [11,12]. Plasmonic excitation to increase solar cell performance is well known.…”
Section: Introductionmentioning
confidence: 99%
“…The embedded of Ag on the DLC lattice prevents the agglomerated nanoparticles and the growth of large and clustered nanoparticles. Our previous reports have shown that the effect of gold and silver nanoparticles in the DLC lattice has led to increased e ciencies in quantum dot solar cells [11,12]. Plasmonic excitation to increase solar cell performance is well known.…”
Section: Introductionmentioning
confidence: 99%
“…The embedded Ag in the DLC lattice prevents the agglomerated nanoparticles and the growth of large and clustered nanoparticles. Our previous reports have shown that the effect of gold and silver nanoparticles in the DLC lattice has led to increased efficiencies in quantum dot solar cells 11,12 .…”
mentioning
confidence: 99%